Simple Investigation on the Optical Properties of Carbon Nanodots Using Lasers and a Lux Meter - Febriani Febriani; Athi' Nur Auliati Rahmah; Bian Itsna Ashfa Al Ashfiya; Juli Astono; Wipsar Sunu Brams Dwandaru (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
Carbon nanodots (Cdots) have excellent optical properties. This study aims to investigate scattering and absorption of Cdots via simple exposure of ultraviolet (UV)/violet, red, and green lasers. The experiment was conducted by preparing the Cdots from cajuput oil distillation wastes as the precursor. The solid wastes were dried under the sun, grounded into powder, filtered, and carbonized inside an oven at 250 oC for one hour. The carbonized powder was then mixed with distilled water, left for a night, and then filtered again so that the Cdots solution was obtained. Here, the mass of the precursor was varied. The Cdots samples were characterized using ultraviolet-visible (UV-Vis) and photoluminescence (PL) spectroscopies, and also particle size analyzer (PSA). The lasers were directly exposed to the Cdots samples. A digital lux-meter was used to measure the intensity of the lasers transmitted from the sample. The angle of the lux-meter was varied on a circular track. The sample was on the center of the track. The UV-Vis characterization showed two peaks at 217 nm and 270 nm, and a tail extending to the visible region. The PL characterization showed an intensity peak at 509.57 nm, which confirms the cyan luminescence of the Cdots. The PSA characterization indicated that the size of the Cdots was 1.04 nm. Moreover, at an angle of 0o, the UV wavelength was strongly absorbed by the Cdots in accordance with the UV-Vis characterization result. The intensity of the green laser also dominates as it was less absorbed and strongly scattered by the Cdots.